PARADIGM OF CHANGES IN THE LEGAL RELATIONSHIP OF CHILDREN'S EDUCATION OUTSIDE THE INDONESIAN LEGAL SYSTEM - MANALU, KARTO (Awang Long Law Review, 2019)
Changes in the legal paradigm of the child marriage outside of marriage with his father in the decision of the Supreme Court (MK) number 46 / PUU-VIII / 2010 raises the pros and cons in the community. For the pro, it is considered appropriate and fulfills a sense of justice for children. Whereas those who contradicted the decision contradicted the Marriage Law which states that children born outside of marriage only have a civil relationship with their mother and family only. The Court considered the legal relationship between the child and his father not solely based on the existence of a marriage bond accompanied by proof of the existence of a blood relationship between the child and the man. The philosophical basis of the paradigm shift in the norms of civil relations between his father's children is a mandate as well as a gift from God Almighty, which we must always guard because in him the dignity, dignity and rights as human beings must be upheld and even extramarital children have the right legal protection. The legal effect of the civil relationship between children outside of marriage and their father to the civil law system in Indonesia is that the state provides guarantees for the position of extramarital children where before the 2010 MK Decision was only considered to have a civil relationship with his mother and family, but after the 2012 MK Decision was deemed to have civil relationship with his father and father's family.